Accent Modification in the Teleconferencing Industry. Issue 1 (2nd January 2018) - Nelson, Kate
Abstract: Within the corporate environment of a teleconferencing call center, hourly paid conference operators (also referred to as "agents") are trained to manage the technical and logistic features of conference calls for corporations located around the globe. In some locations, these employees are candidates for accent modification training due to the presence of a strong regional or foreign accent. While most employees understand the need for accent modification training within this environment, some may take a defensive stance regarding a recommendation from management to become involved in an accent modification training program. The discussion prior to training must be handled with sensitivity, and it is the Accent Modification Instructor's challenge to present accent modification in such a way that employees do not feel as though their cultural or ethnic identity is being attacked or that their speech is deemed as substandard; however, changes surrounding an employee's speech may be necessary in order to comply with the communication standards set forth by the corporation with which they are employed.